Thermoplastic Starch Composites Filled With Isometric and Elongated TiO2-Based Nanoparticles - Ujcic, Aleksandra; Nevoralova, Martina; Dybal, Jiri; Zhigunov, Alexander; Kredatusova, Jana; Krejcikova, Sabina; Fortelny, Ivan; Slouf, Miroslav (Frontiers in Materials, 2019)
Biodegradable thermoplastic starch (TPS) composites with isometric titanium dioxide nanoparticles (TiO2; diameter  100 nm) and elongated titanate nanotubes (TiNT; diameter  20 nm and aspect ratio >50) were prepared from wheat and tapioca starch. The preparation was based on our recently developed two-step procedure consisting of the solution casting (SC) followed by the melt mixing (MM), which had been shown to yield highly homogeneous TPS in our previous study. In this work we demonstrated that the type of the TPS matrix and the type of the filler had significant impact on the morphology and the properties of the final composites. Multiple microscopic techniques (LM, SEM and TEM) evidenced that the TPS/TiO2 composites exhibited a very homogeneous dispersion of the filler, while the TPS/TiNT composites contained micrometer-size agglomerates of TiNT. Moreover, all composites with the wheat starch matrix (TPS(w)) showed a higher filler agglomeration than the corresponding composites with the tapioca starch matrix (TPS(t)). Rheological experiments showed that the TiO2 and TiNT fillers had quite small impact on the viscosity of the TPS(w) matrix, probably due to slightly higher agglomeration, poorer dispersion and weaker matrix-particle interactions. On the other hand, the TPS(t) matrix was influenced by both fillers significantly: the TiO2 nanoparticles with almost ideal dispersion formed a physical network in the TPS(t) matrix, which significantly increased the viscosity of the composite, whereas the TiNT nanotubes seemed to destruct the TPS(t) matrix partially, resulting in decreased viscosity of the composite. DMTA results confirmed the rheological measurements: Storage moduli (G') showed that TPS(t) and its composites with TiO2 were stiffer than the corresponding TPS(w) samples, while the TPS(t)/TiNT composites were less stiff than TPS(w)/TiNT. Also loss moduli (G") confirmed the difference between tapioca starch and wheat starch composites, which differed by their glass transition temperatures (Tg of TPS(w) < Tg of TPS(t)). The rheological and DMTA results were supplemented and supported by IR, XRD and TGA measurements.